2020
DOI: 10.1371/journal.pone.0240228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative test-retest variability of outcome parameters derived from brain [18F]FDG PET studies in non-human primates

Abstract: Introduction Knowledge of the repeatability of quantitative parameters derived from [ 18 F]FDG PET images is essential to define the group size and allow correct interpretation. Here we tested repeatability and accuracy of different [ 18 F]FDG absolute and relative quantification parameters in a standardized preclinical setup in nonhuman primates (NHP). Material and methods Repeated brain [ 18 F]FDG scans were performed in 6 healthy NHP under controlled experimental factors likely to account for variability. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Because a fair comparison of new preclinical PET systems based on NEMA standard evaluations has been questioned [ 26 ], we further studied the performances of the IRIS XL-220 PET system in real conditions using two distinct radiotracers. The images obtained from the 18 F-FDG and (-)-[ 18 F]FEOBV experiments on NHP were consistent with previous reports, with (-)-[ 18 F]FEOBV binding corresponding to the biodistribution of the vesicular acetylcholine transporter [ 20 , 27 , 28 ]. This revealed that the IRIS XL-220 PET provided an excellent quality of images in NHP, but also in rats based on the spatial resolution of the system.…”
Section: Discussionsupporting
confidence: 90%
“…Because a fair comparison of new preclinical PET systems based on NEMA standard evaluations has been questioned [ 26 ], we further studied the performances of the IRIS XL-220 PET system in real conditions using two distinct radiotracers. The images obtained from the 18 F-FDG and (-)-[ 18 F]FEOBV experiments on NHP were consistent with previous reports, with (-)-[ 18 F]FEOBV binding corresponding to the biodistribution of the vesicular acetylcholine transporter [ 20 , 27 , 28 ]. This revealed that the IRIS XL-220 PET provided an excellent quality of images in NHP, but also in rats based on the spatial resolution of the system.…”
Section: Discussionsupporting
confidence: 90%
“…In humans and macaques, the volume of the pituitary gland is small, and under physiological conditions, its metabolic activity is comparable to the background level of the entire brain (16, 17) . The 18 F-FDG uptake of the pituitary gland may even be underestimated due to the partial-volume-effects that affect the emission signal recovery (16) .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis was performed in VivoQuant 4.5 (Invicro, Boston, USA). Based on repeatability parameters for correct interpretation of the results, a standardized uptake value (SUV) ratio was used for robustness (17, 42) . An increased uptake, and pituitary gland hypermetabolism is defined as a SUV mean ratio above 1.5 for the pituitary gland over the surrounding brain in combination with a SUV peak ratio above background levels (>1.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when normalizing values to a (pseudo-reference) region, we were unable to identify whether regional hypo/hypermetabolism truly reflects decreased/increased metabolism or is driven by absolute metabolic changes in the surrounding GM regions. Although methods exist to approach absolute quantification ( 55 ) (e.g., determining plasma kinetics with an arterial-plasma input function), they are invasive and unnecessary in clinical examinations. Third, since no MR data were available, we were unable to perform partial volume correction, which may have influenced our results, especially by chemotherapy-induced volumetric effects or aging in longitudinal follow-up ( 40 , 56 ).…”
Section: Discussionmentioning
confidence: 99%